Mārā Jīkākā, māruṃ Rāṇapura : prakhara patrakāra, ājīvana lokasevaka, ane laḍavaiyā Śrī Amrtalāla Śeṭhanā jīvanakāryanī ūrmisabhara jhalaka - Mehta, Labhuben Mohanlal, 1915- (Abhinava Bhāratī Prakāśana, 1979)
The author's reminiscences about Amrtalāla Dalapatabhāī Śeṭha, b. 1891, Gujarati journalist and freedom fighter.